Art autochtone : langue, oralité, communication : introdution au dossier - Vigneault, Louise (RACAR : Revue d'art canadienne / Canadian Art Review, 2016)
Native languages in Canada are closely tied to memory and territory. Their weakening or disappearance, along with the decrease of the oral transmission of knowledge, has therefore directly impacted the set of semiotic and epistemological codes on which cultures rest. Split between their language of origin and the country’s majority languages, and lacking any political or legislative leverage, communities have progressively lost their means to self-fulfillment. In the Canadian linguistic divide, French-speaking Native communities have found themselves doubly marginalized. Today, artistic creations play a crucial role in the renewal of movements focused on transmission, mediation, and dialogue; they make the unspoken visible and open up new possibilities of expression. For the artists, speaking the language and referring to its reality is an act through which the collective imagination is reclaimed and a spatial and historical anchoring is reactivated. The contributors to this journal’s latest and decidedly polemical section examine these realities and lift the veil on certain lines of thought that have been ignored or too quickly discarded.